Penerapan media religiosity lab book (RLB) untuk meningkatkan kesadaran keberagaman agama siswa - Nurlaili Dina Hafni , Nurlaili Dina Hafni; Kafiyatul Muthoharoh, Kafiyatul Muthoharoh; Roichatul jannah, Roichatul jannah; Erisa Dwi Septiani , Erisa Dwi Septiani (Joyful Learning Journal, 2025)
This study aims to enhance religious diversity awareness among 2E grade students at MI Hidayatun Najah Tuban through the implementation of the Religiosity Lab Book (RLB) media. This media is designed to help students understand the concept of religious diversity in an interactive and enjoyable way. The study uses Classroom Action Research (CAR) with a cyclical design consisting of planning, action, observation, and reflection. The research subjects were 28 students from class 2E at MI Hidayatun Najah Tuban who participated in the learning process using the RLB media. Data collection techniques included observation, interviews, tests, and documentation. The results of the study show that the implementation of RLB media effectively improves students’ understanding of religious diversity and fosters attitudes of tolerance among religious communities. This improvement is reflected in test results indicating increased student comprehension before and after using the RLB media, as well as changes in students’ attitudes to be more open and appreciative of religious differences. This study is expected to contribute positively to efforts in developing religious diversity learning at the elementary school level, particularly in creating a more inclusive and harmonious environment.